Analisa Kekuatan Poros Komposit Polyester Serat Batang Pisang Yang Disusun Simetri 20^O 40^O 60^O Terhadap Pengujian Puntir - Irianto, Agus Wahyudi (2016)
The purpose of this study was to describe the power of banana stem fiber composite shaft bermatrik polyester against torsion testing and describing the macro image torsional fracture after testing. The initial process of peeling bark peeled banana with a 1m length of 4 layers of outer skin, prose continued pressing and soaking midrib banana stems for 1 bulan.Setelah the electoral process the fiber strand by strand using clean water. Drying the fiber in the sun to dry subsequent immersion process with potassium permangate (KMnO4) 2% per 1 liter of distilled water in a 2-hour soaking time. Drying is performed at room temperature followed the oven at 35 0C for 1 jamhingga water content of 10%. Hand lay-up methods are used in the manufacture of composites with fiber direction 200 / -200, 400 / -400 and 600 / -600 and 157 series using polyester resin BQTN against puntir.Pengujian testing is used to describe the torsional strength and observe macro photos shaft fracture polyester composite fiber banana stems. The test results can be concluded phenomenon highest torsional strength at the angular orientation of test 400 that is the power puntirnya 0503 kg / mm2. On the results of the macro image visible fault structure on each composite specimen irregular and bumpy, this is caused because the composite has liat.void existing properties will experience a pull-out fiber which dominates the torsional strength will decrease.